(untitled) (Nativa, 2024)
ABSTRACT: Coffee, a globally traded and profitable commodity, is pivotal in many countries’ economies and social development. In the Vale do Ribeira, a region of significant socio-environmental importance, coffee farming has the potential to boost local family agriculture through the diversification of agricultural production, with a focus on Conilon coffee (Coffea canephora Pierre), which thrives in hot and humid climates. In this context, our study’s in situ evaluation of the agronomic performance of Conilon coffee clones is of utmost importance. We assessed the vegetative growth, incidence of pests and diseases, productivity, and grain ripening of various Conilon coffee clones in Registro, located in the humid subtropical environment of Vale do Ribeira. Clones 401 and 410 demonstrated superior vegetative growth. Pests and diseases, such as leaf miner, Phoma, and Cercosporiosis, were more prevalent during higher temperatures, while rust was a concern in cooler temperatures. The most productive clones were 13V, 407, 403, and 409, with a higher percentage of grains in the "cherry" stage, making them the most promising for cultivation in the region. Keywords: brown eye spot; leaf miner; Mata Atlântica; plant growth; yield. Desempenho agronômico de clones de café conilon submetidos ao clima subtropical úmido do Vale do Ribeira RESUMO: O café é uma das commodities mais negociadas e lucrativas globalmente, desempenhando um papel crucial na economia e no desenvolvimento social de muitos países. No Vale do Ribeira, uma região de grande importância socioambiental, a cafeicultura tem potencial para favorecer a agricultura familiar local através da diversificação da produção agrícola, com ênfase no café conilon (Coffea canephora Pierre), que é adaptado a ambientes de clima quente e úmido. Nesse contexto, a avaliação in situ do desempenho agronômico de clones de café conilon é essencial para identificar as opções mais promissoras. O presente estudo avaliou o crescimento vegetativo, a incidência de pragas e doenças, a produtividade e a maturação de grãos de diferentes clones de café conilon em Registro, localizado no ambiente subtropical úmido do Vale do Ribeira. Os clones 401 e 410 se destacaram pelo crescimento vegetativo superior. Em relação às pragas e doenças, houve maior incidência de bicho mineiro, Phoma e Cercosporiose durante períodos de temperatura mais elevada, enquanto a ferrugem foi mais relevante em temperaturas amenas. Os clones mais produtivos foram 13V, 407, 403 e 409, apresentando maior porcentagem de grãos no estágio “cereja”, sendo considerados os mais promissores para o cultivo na região. Palavras-chave: cercosporiose; bicho mineiro; Mata Atlântica; crescimento vegetativo; produtividade.